Comparison Between Automated and Manual Sphygmomanometer for Measuring Blood Pressure in Children - Taksande, A; Jadhav, A; Vagha, J (Journal of Nepal Paediatric Society, 2015)
Introduction: The mercury sphygmomanometer has been the gold standard used for obtaining blood pressure (BP). However, due to environmental concerns and more use of automated BP devices, an alternative to using the standard mercury sphygmomanometer to measure BP. The aim of this study is to evaluate the accuracy of the Automated (Omron) BP device against the mercury sphygmomanometer in children. Material and Methods: One hundred children were enrolled in this study. The accuracy of Omron HEM–7121 BP readings was compared with that of mercury BP device readings. Each children had four BP measurements recorded sequentially i.e. two valid systolic readings, and two valid diastolic readings. Results: BP taken with the automated device was systolic 109.77 ± 9.97 and diastolic 74.50 ± 8.32 mm Hg compared to systolic 112.68 ± 9.98 and diastolic 77.38 ± 7.91 mm Hg measured by manual mercury sphygmomanometer BP readings (p<0.001). Automated and mercury BP measurements were correlated (r = 0.89, systolic BP; r = 0.82, diastolic BP). Linear regression analysis showed that the automated systolic BP is a significant predictor (? = 0.897, p < 0.001) of manual systolic BP. Similarly, automated diastolic BP was also a significant predictor (? = 0.829, p< 0.001) of manual diastolic BP. Conclusion: This study concludes that the automated BP device is reliable and accurate for measuring the BP in children. J Nepal Paediatr Soc 2015;35(1):13-17